Γδ T Cells and dendritic cells in refractory Lyme arthritis. Issue 4 (20th January 2015) - Divan, Ali; Budd, Ralph C.; Tobin, Richard P.; Newell‐Rogers, M. Karen
Abstract : Review on TLR signaling and antigen processing, presentation between γδ T cells and dendritic cells, both which contribute to refractory Lyme arthritis. Abstract : Lyme disease is a multisystem infection transmitted by tick vectors with an incidence of up to 300, 000 individuals/yr in the United States. The primary treatments are oral or i.v. antibiotics. Despite treatment, some individuals do not recover and have prolonged symptoms affecting multiple organs, including the nervous system and connective tissues. Inflammatory arthritis is a common symptom associated with Lyme pathology. In the past decades, γδ T cells have emerged as candidates that contribute to the transition from innate to adaptive responses. These cells are also differentially regulated within the synovia of patients affected by RLA. Here, we review and discuss potential cellular mechanisms involving γδ T cells and DCs in RLA. TLR signaling and antigen processing and presentation will be the key concepts that we review in aid of understanding the impact of γδ T cells in RLA.